EFIKASI DIRI, BEBAN KERJA DAN KEPUASAN SEBABAI FAKTOR PENENTU KINERJA PEGAWAI - Rofi, Akhmad Nur (ECONBANK: Journal of Economics and Banking, 2019)
Every employee in an organization will do the work in accordance with the responsibilities given to employees. The purpose of this research was to analyze the influence of self-efficacy, workload and job satisfaction on the performance of employee of PJN Metropolitan Semarang Region. Data collection was carried out by distributing questionnaires to 35 employees using the census method. Multiple linear regression analysis techniques are used to analyze the data in this research. The results show that the self-efficacy, satisfaction and workload affect employee performance. The self-efficacy factor is the variable that gives the most dominant influence on the performance of employees of the PJN Metropolitan Semarang Region. Self-efficacy or one's belief in achieving performance makes a person have a high desire in carrying out his obligations and responsibilities as an employee. Employees who are satisfied with their work will voluntarily do their jobs so they can improve their performance. While the workload that is too heavy for employees will result in employees not focusing on doing work so that it can reduce performance. Therefore, to improve the performance of company employees must pay attention to factors of self-efficacy, job satisfaction and workload of employees